Montenegro as a State Governed by the Rule of Law: Valtazar Bogišić’s Character and Contributions in Italian Travel Accounts at the Turn of the 19th and 20th Centuries - Popović, Olivera (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2024)
During the late nineteenth and early twentieth centuries, a significant number of Italian travellers were drawn to the Principality of Montenegro, primarily motivated by their curiosity about the homeland of their future queen, Jelena Petrović Njegoš, who wed Prince Victor Emmanuel III of Savoy in October 1896. The majority of these travellers, predominantly journalists, meticulously documented their experiences through travel narratives that were initially published as newspaper articles and subsequently compiled into books. These authors notably emphasized Montenegro’s legal developments, accomplished within a mere two decades following its international recognition as an independent nation. They attributed this remarkable progress to Valtazar Bogišić (1834-1908), a jurist, legal scholar, and ethnographer who came from the Konavle region near Dubrovnik. Bogišić, a Slavophile with a comprehensive education acquired at various European universities, also held the position of Minister of Justice in Montenegro. The primary aim of this case study is to analyze how various Italian authors portrayed Minister Bogišić to their readers across the Adriatic, elucidating the information they presented regarding the legal code he had crafted for Montenegro. Additionally, we delve into the significance of this legal code, which was subsequently translated into several foreign languages. In addition to presenting Valtazar Bogišić and his work, Italian authors also constructed an image of Montenegro as a state governed by the rule of law. They achieved this portrayal by referring to the Montenegrin rulers who, through the enactment of the first Montenegrin legal codes, orchestrated a profound transformation within Montenegrin society. From their perspective, Montenegro, which was originally rooted in customary law within a tribal framework, underwent a transition into a principality governed by a comprehensive system of written laws. This transformation is primarily exemplified by Bishop Petar I Petrović Njegoš and Prince Danilo Petrović Njegoš, whose pioneering endeavours in legal codification captured the attention of several Italian authors. The overarching objective of this paper is to discern the purpose behind the production of such an image of Montenegro, which became prominent in the Italian travel writing tradition in the late 19th century, and to seek to identify the factors that influenced the formation of this representation.